(untitled) (Journal of Hama University, 2021)
Recently, esthetic concerns has been increased dramatical for pediatric patient and their parents for the dental treatment, this study was conducted to clinicaly evaluate two type of esthetic primary molars crowns fabricated using two different methods, PMMA White Peaks blocks via Computer Aid Designed, Computer Aid Manufacturing CADsystem and direct composite colloid crowns in restoring pulp treated primary molars for restoration failure, gingival health and marginal integrity. Twenty five pulp treated primary molars prepared for crowning, in group A: After tooth preparation, digital scanning for its dies was made and then digital design via “Exucade software ” to fabricate crowns using polymethylmethacrylate (PMMA) blocks, the crowns were cemented to the prepared teeth cement., in group B (the direct technique): direct composite resin were applied via celluloid ready-made matrix , the follow-up were recorded in 3-6-12 months. No statistically significant differences noted when using Chi-square Test in terms of restoration failure evaluation between Group A(P= 0.146), statistical significance differences were noted in gingival health, marginal integrity when using mann-whiteny test (p=0.034 – p=0.009). The two tested esthetic crowns are prone to be able to be used clinically with no statistical differences between the two types, with 97% retention rate for direct composite via colloid matrix compared to 80% in CADcrowns, although, PMMA crowns perform better in the aspect of gingival health and marginal integrity in late follow-up periods.